COVID-19 vaccine skeptics are persuaded by pro-vaccine expert consensus messaging - Białek, M.; Meyers, E. A.; Arriaga, P.; Harateh, D.; Urbanek, A. (Journal of Experimental Psychology - Applied, 2023)
To further understand how to combat COVID-19 vaccination hesitancy, we examined the effects of pro-vaccine expert consensus messaging on lay attitudes about vaccine safety and intention to get a COVID-19 vaccine. We surveyed 729 unvaccinated individuals from four countries in the early stages of the pandemic and 472 unvaccinated individuals from two countries after 2 years of the pandemic. We found belief of vaccine safety strongly correlated with intention to vaccinate in the first sample and less strongly in the second. We also found that consensus messaging improved attitudes toward vaccination even for participants who did not believe the vaccine is safe nor intended to get it. The persuasiveness of expert consensus was unaffected by exposing participants’ lack of knowledge about vaccines. We conclude that highlighting expert consensus may be a way to increase support toward COVID-19 vaccination in those hesitant or skeptical.